The diamond of Darkhold - DuPrau, Jeanne (New York Random House, 2008)
Lina and Doon are returning to the city of Ember, but what awaits them in the dark? This highly acclaimed adventure series is a modern-day classic--with over 4 MILLION copies sold!
Includes index
Keywords: Tham khảo